Stable isotope modeling of the groundwater discharge in complex watersheds of the state of São Paulo, Brazil - Santarosa, Lucas Vituri [UNESP] (2022)
The increasing pressure on water resources demands integrated and multidisciplinary approaches to address environmental, scientific, and social issues related to water availability in watersheds. In large watersheds, many factors control hydrologic processes, requiring the application of a methodology able to describe water dynamics in complex situations. This study uses stable isotope (2H and 18O) modeling to characterize the groundwater contribution in an area of heterogeneous hydrogeological framework and advanced anthropization, located in the Piracicaba-Capivari-Jundiaí (PCJ) and Tietê-Jacaré (TJ) water management units – central-eastern portion of the state of São Paulo, Brazil. Groundwater dynamics are controlled by the direct interaction of the rainfall regime with hydrogeological domains. The modeling in this study indicates that some 60–80% of the total streamflow volume comes from groundwater. However, in the crystalline domain, the aquifer capacity for surplus water storage is smaller, increasing the importance of rainfall for generating direct runoff and maintaining the streamflow. For this characteristic, the PCJ unit is more dependent on surface water and vulnerable to prolonged droughts. On the other hand, in the sedimentary areas, the contribution of groundwater discharge is around 80%, showing that the aquifer storage capacity guarantees homogenization of the discharge throughout the year, and ensures water security in drought periods. It is concluded that the successful application of stable isotope modeling in large basins. The method, combined with others already established, can add a more dynamic and sensitive set of information for understanding hydrological processes in complex hydrographic basins, with heterogeneous hydrogeological structures and the effects of anthropic action.